Analysis of the Mental Health Status and Influencing Factors of Community Health Service Personnel under the Normalization of Epidemic Prevention and Control - Li, Jianhui; Zhou, Zhiwei; Lian, Siyu (International Journal of Social Sciences and Public Administration, 2025)
Objective To understand the mental health status and influencing factors of community health service personnel under the normalization of epidemic prevention and control, and to provide reference for the formulation of psychological intervention programs in the later stage. Methods 200 community health service workers in Guangdong Province were selected by convenient sampling method, and the general situation questionnaire and symptom self-assessment scale (SCL-90) were used. Results The total score of SCL-90 was 112.39 ± 33.31; univariate analysis showed that the position was statistically significant for SCL-90 scores (P <0.05); regression analysis showed that the position was an important factor affecting the mental health status of community health service personnel (P <0.05). Conclusion Under the normalization of epidemic prevention and control, community health service personnel have a certain degree of psychological distress, and the psychological conditions of medical staff with different characteristics are different. Therefore, high attention should be paid to the mental health status of medical staff, and their psychological support and counseling should be strengthened.